Differential herbicide persistence and shifts in soil bacterial communities in Alfisol and Inceptisol - Amarachi Grace Nwokocha; Sani Idris; Adeniyi Ogunjobi; Olajire Fagbola; Sonny T.M. Lee (Universitas Sebelas Maret, 2025)
Weeds significantly reduce crop yields and promote herbicide use, accounting for 80% of agricultural pesticides. However, herbicide persistence and toxicity adversely affect soil microbial communities, impacting soil health and productivity. This study compared the effects of organic (Vinegar-weed-care: acetic acid) and chemical herbicides (PrimextraGold: Atrazine + S-metolachlor; Imazapyr: Isopropyl amine) on soil bacteria in Alfisol and Inceptisol from Ibadan, Nigeria. Soils were analysed for physical properties and microbial DNA, and herbicide degradation was tracked using GC-MS at 0, 4, 8, and 12 weeks. Alfisol exhibited higher fertility with pH 6.2, organic carbon 3.9 g kg-1, nitrogen 0.7 g kg-1, and phosphorus 25.9 mg kg-1, compared to Inceptisol (pH 5.5, organic carbon 1.9 g kg-1, nitrogen 0.6 g kg-1, phosphorus 20.8 mg kg-1). Herbicide persistence was greater in Alfisol: metolachlor (84.94%) and Imazapyr (61.00%) vs. Inceptisol (52.55% and 50.15%, respectively). Organic herbicide metabolites also persisted more in Alfisol (35.13%) than in Inceptisol (28.00%). In non-sterile Alfisol, biodegradation of PrimextraGold and Imazapyr was lower (43.46% and 10.30%) than in sterile soils (53.97% and 16.17%), while the organic herbicide biodegraded more in non-sterile (23.49%) than in sterile (17.08%). In non-sterile Inceptisol, Imazapyr degraded less (8.94%–31.72%) than in sterile (29.49%–34.75%), but atrazine degraded more in non-sterile (61.96%–68.17%). Organic acetamide degraded better in non-sterile Inceptisol (23.42%–90.5%) than in sterile (12.47%–30.7%). Chemical herbicides reduced Candidatus Udaeobacter, Pedosphaera, and Chthoniobacter in Alfisol, while organic herbicides enhanced them in both soils. These findings highlight the ecological benefits of soil-friendly organic herbicides.